2008
DOI: 10.1177/1049909108315515
|View full text |Cite
|
Sign up to set email alerts
|

Using the LCP: Bereaved Relatives' Assessments of Communication and Bereavement

Abstract: The Liverpool Care Pathway (LCP) is aimed at improving care and communication in the dying phase. The authors studied whether use of the LCP affects relatives' retrospective evaluation of communication and their level of bereavement. An intervention study was conducted. During the baseline period, usual care was provided to dying patients. During the intervention period, the LCP was used for 79% of the patients. In total, bereaved relatives filled in a questionnaire for 57% of the patients, on average 4 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The results from qualitative studies [33-35] and from experimental assessments in non-randomized trials [36,37] seem to suggest that the LCP Program can improve significantly, and over long-term, the quality of end-of-life care delivery in hospitals and other care settings. According to the MRC Framework, published research on the LCP completed the first three phases, from preclinical phases to phase II.…”
Section: Discussionmentioning
confidence: 99%
“…The results from qualitative studies [33-35] and from experimental assessments in non-randomized trials [36,37] seem to suggest that the LCP Program can improve significantly, and over long-term, the quality of end-of-life care delivery in hospitals and other care settings. According to the MRC Framework, published research on the LCP completed the first three phases, from preclinical phases to phase II.…”
Section: Discussionmentioning
confidence: 99%
“…By addressing the questionnaires "to family of" the deceased patient, it is likely that many of the questionnaires did not reach appropriate respondents. Further, although this kind of response rate is common in after-death surveys and interviews of family respondents, [35][36][37] caution must be exercised in generalizing the results. In analyses using the same database, we found differences in both the characteristics and the care of decedents for patients who had a family member who responded compared with those who did not.…”
Section: Role Of Sponsorsmentioning
confidence: 99%
“…Whilst these end-of-life care tools are UK-based developments, their use internationally would present an additional opportunity to develop such knowledge -a process that has already started with the implementation of the LCP. 30 Whatever the system and wherever the system is implemented, bringing about change raises similar issues of process and a similar need to demonstrate outcomes. Until such outcomes are defined future studies should utilize the explicit outcomes identified by this review which include: the resident's documented place of death; the number of crisis admissions to hospital in their last six months of life; and the presence of a documented ACP and DNAR form.…”
Section: Discussionmentioning
confidence: 97%